Preparation and Thermal Properties of Eutectic Hydrate Salt Phase Change Thermal Energy Storage Material - Lin Liang; Xi Chen (International Journal of Photoenergy)
In this study, a new cold storage phase change material eutectic hydrate salt (K2HPO4·3H2O–NaH2PO4·2H2O–Na2S2O3·5H2O) was prepared, modified, and tested. The modification was performed by adding a nucleating agent and thickener. The physical properties such as viscosity, surface tension, cold storage characteristics, supercooling, and the stability during freeze-thaw cycles were studied. Results show that the use of nucleating agents, such as sodium tetraborate, sodium fluoride, and nanoparticles, are effective. The solidification temperature and latent heat of these materials which was added with 0, 3, and 5 wt% thickeners were −11.9, −10.6, and −14.8°C and 127.2, 118.6, 82.56 J/g, respectively. Adding a nucleating agent can effectively improve the nucleation rate and nucleation stability. Furthermore, increasing viscosity has a positive impact on the solidification rate, supercooling, and the stability during freeze-thaw cycles.